Transcriptome and Metabolome Analyses of Flavonoid Biosynthesis During Berry Development of Muscadine Grape (Vitis rotundifolia Michx) - Qiaofeng Yang; Changlin Li; Yan Wang; Xian Pei; Aixin Wang; Li Jin; Linchuan Fang (Plants)
Flavonoids play a crucial role in plant development, resistance, and the pigmentation of fruits and flowers. This study aimed to uncover the mechanism of flavonoid biosynthesis and fruit coloring in muscadine grapes. Two muscadine genotypes (Paulk and Supreme) were investigated via metabolomic and transcriptomic analysis during three developmental stages (bunch closure, veraison stage, and ripening stage). A total of 314 flavonoids were identified, with flavones and flavonols being the primary constituents. The contents of many differentially accumulated metabolites (DAMs) were higher at the veraison stage. The total anthocyanin content was upregulated during berry development, with the dominant type of anthocyanidin-3,5-O-diglucoside. Proanthocyanins accumulated higher levels in the ripening stage of Paulk than Supreme. Transcriptomic analyses revealed that over 46% of the DEGs exhibited higher expression levels in the bunch closure stage. Moreover, phenylalanine ammonia-lyase (PAL), cinnamyl 4-hydroxylase (C4H), and coumaryl CoA ligase (4CL) genes were upregulated during berry development, suggesting they promote second metabolites biosynthesis. The upregulation of dihydroflavonol 4-reductase (DFR) and leucoanthocyanin reductase (LAR) may related to the higher levels of PA in Paulk. Anthocyanidin synthase (ANS) and UDP-glucose:flavonoid-3-O-glucosyltransferase (UFGT) showed higher expression levels in the ripening stage, which may relate to the accumulation of anthocyanidins. This study provides comprehensive insights into flavonoid metabolism and berry coloration in Vitis rotundifolia.